Effects of kettlebell swing training on cardiorespiratory and metabolic demand to a simulated competition in young female artistic gymnasts - Xavier Melo; Inês Arrais; João Luís Marôco; Pedro Neto Ribeiro; Sara Nabais; Raquel Coelho; Joana Reis; Vítor Angarten; Bo Fernhall; Helena Santa-Clara (PLoS ONE, 2023)
We examined the effects of adding a Kettlebell Swing training program (KB) to the regular skill-training protocol (REGULAR) on cardiorespiratory fitness, cardiorespiratory/metabolic demand, and recovery to a simulated competition of female artistic gymnastics. Nine gymnasts (13±2 years) had their REGULAR complemented with a 4-week kettlebell training (REGULAR+KB), consisting of 3 sessions/week of 12x30” swings x 30” rest with ¼ of their body weight, while 9 aged-matched gymnasts acted as a comparison group. Peak oxygen uptake (